Dose-Dependent Effects and Reversibility of the Injuries Caused by Nandrolone Decanoate in Uterine Tissue and Fertility of Rats - Belardin, Larissa Berloffa [UNESP]; Simao, Vinicius Augusto [UNESP]; Araujo Leite, Gabriel Adan [UNESP]; Almeida Chuffa, Luiz Gustavo de [UNESP]; Cherici Camargo, Isabel Cristina [UNESP] (Wiley-Blackwell, 2014)
This study is the first to investigate the effects of different doses of nandrolone decanoate (ND) upon uterine tissue and fertility, and if the reproductive alterations can be restored after cessation of the treatment. Wistar female rats were treated with ND at doses of 1.87, 3.75, 7.5, and 15mg/kg body weight, diluted in vehicle (n = 30/group), or received only mineral oil (control group, n = 45). The animals were divided into three periods of study: ND-treated receiving a daily subcutaneous injection for 15 consecutive days (1), and treatment with ND followed by 30-day recovery (2), and 60-day recovery (3). At the end of each period, five females per group were induced to death to histopathological analysis and the others were allowed to fertility evaluation (at 19th gestational day). Animals that received ND followed by 30-day recovery exhibited persistent diestrous and marked suppression of reproductive capacity. Conversely, after 60-day recovery, only lowest doses females (1.87 and 3.75mg/kg) exhibited restoration of normal estrous cyclicity. Uterine weights were increased after ND treatment similarly to that of the controls after 60-day recovery. The ND-treated groups showed histopathological changes in the endometrium, myometrium, and perimetrium, and an increase in the thickness of both muscular and serous layers. Notably, the recovery of uterine tissue after ND treatment was dose- and period-dependent. We reported that administration of ND promoted damage in uterine tissue and fertility of rats, and the recovery periods were insufficient to restore all of the side effects caused by ND under a dose-dependent response
Keywords: reproductive toxicology; nandrolone decanoate; histomorphometry; recovery period; uterus; rats; fertility